Potential for production of biogas from waste arising from the creation of tilapia in the aquaponic system (Research, Society and Development, 2020)
The objective of this work was to quantify the generation of waste from tilapia farming in an intensive system with water recirculation, and to evaluate the use of this waste in the biodigestion process for biogas production. The scientific methodology used in this experiment was a research at the laboratory level using the quantitative method. The aquaponic system used has a capacity for 200 fish and 144 lettuces, consisting of two rearing tanks, a pumping and heating tank, a decanter and a biological filter. Each breeding tank has a volume of 1000 L and the population density of fish was 100 fish m-3. Vegetable cultivation was carried out using an NFT (Nutrient Film Technique) system. The biodigesters were built using plastic gallons with a volume of 50 L and the biodigestion time was 35 days. The volume of decanted waste from the intensive fish farming system with recirculation is low, therefore, the process of separating wastewater from waste must be very well conducted to provide the largest possible volume for biodigestion. The biodigestion of tilapia waste in an intensive system with recirculation proved to be feasible, with productivity equivalent and even superior to other works carried out with waste from other fish species. Biodigestion proved to be an alternative for the treatment of the effluent generated in the creation of tilapia in an aquaponic system. The temperature of the biodigester and the retention time directly influenced the production of biogas with tilapia waste.